2020
DOI: 10.1002/jor.24717
|View full text |Cite
|
Sign up to set email alerts
|

Proximal‐distal shift of the center of rotation in a total wrist arthroplasty is more than twice of the healthy wrist

Abstract: Reproduction of healthy wrist biomechanics should minimize the abnormal joint forces that could potentially result in the failure of a total wrist arthroplasty (TWA). To date, the in vivo kinematics of TWA have not been measured and it is unknown if TWA preserves healthy wrist kinematics. Therefore, the purpose of this in vivo study was to determine the center of rotation (COR) for a current TWA design and to compare its location to the healthy wrist. The wrist COR for six patients with TWA and 10 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
(120 reference statements)
0
17
0
Order By: Relevance
“…Understanding the natural axes of a joint is crucial for novel prosthetic and arthroplasty design (Brumbaugh et al, 1982;Stokdijk et al, 2000) and musculoskeletal modelling (Goislard De Monsabert et al, 2018), as the success of these techniques depends on replicating normal joint kinematics. Axes of rotation have been used to validate arthroplasty design (Hooke et al, 2015), and assess joint function (Pothrat et al, 2015), quantify joint instability (Duck et al, 2003), to determine appropriate joint modelling simplifications (Sheehan, 2010), classify joint pathology (Wolf and Degani, 2006), and determine joint centres of rotation with the aim of improving rehabilitation activities and reduce arthroplasty failure (Akhbari et al, 2020;Amabile et al, 2016). Thus, it is vital that the description of the axes and their relationship to each other in vivo is understood.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the natural axes of a joint is crucial for novel prosthetic and arthroplasty design (Brumbaugh et al, 1982;Stokdijk et al, 2000) and musculoskeletal modelling (Goislard De Monsabert et al, 2018), as the success of these techniques depends on replicating normal joint kinematics. Axes of rotation have been used to validate arthroplasty design (Hooke et al, 2015), and assess joint function (Pothrat et al, 2015), quantify joint instability (Duck et al, 2003), to determine appropriate joint modelling simplifications (Sheehan, 2010), classify joint pathology (Wolf and Degani, 2006), and determine joint centres of rotation with the aim of improving rehabilitation activities and reduce arthroplasty failure (Akhbari et al, 2020;Amabile et al, 2016). Thus, it is vital that the description of the axes and their relationship to each other in vivo is understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observed a functional outcome which was marked better than function in the affected opposite wrist. A newest TWA study revealed that the center of motion for extension-flexion in TWA is localized in the proximal third of capitate similar to a healthy wrist, whereas the center of motion for radial-ulnar deviation in TWA is localized in contrast to a healthy wrist at the distal tip of capitate [56]. The question is: Does placement of both screws for fixation a carpal TWA component with convergence to distal into the capitate directly aligned to the two centers of motion in the absence of rigid fixation the carpal plate along the entire width of carpus and without crossing a carpometacarpal joint improve function and decrease the risk of loosening?…”
Section: Discussionmentioning
confidence: 99%
“…There exists still a controversy about the existence of a "center of rotation" of the wrist. If one exists it will be found in the head of the capitate, for both FE and RUD [3,[36][37][38][39].…”
Section: Overall Motionmentioning
confidence: 99%